Role of ethics, meritocracy, and professionalism in public sector reforms: A Q methodology study - Munshi Muhammad Abdul Kader Jilani; Samira Tasnim; Nahian Rahman; A S M Rafad Asgar; Nasim Ahmed (PLoS ONE, 2026)
Public sector reforms are crucial for improving governance efficiency, accountability, and service delivery. Their success, however, hinges on key factors such as ethics, meritocracy, and professionalism. This study utilizes Q methodology to explore various perspectives on public sector reforms, drawing on New Public Management (NPM) theory to identify critical priorities and challenges in reform implementation. By employing a structured sorting technique, the study captures stakeholders’ subjective viewpoints in governance and public administration, revealing six distinct perspectives. The findings highlight the vital role of ethical governance (Factor 1) in fostering transparency and public trust while also stressing the importance of strong political will to reduce political interference (Factor 2). Furthermore, the institutionalization of meritocracy and professionalism (Factor 3) is essential for improving administrative efficiency, minimizing bureaucratic inefficiencies, and creating clear career pathways. A collaborative approach that incorporates civil society and private-sector engagement (Factor 4) is also deemed necessary for sustaining reform efforts. However, deeply rooted bureaucratic cultures and institutional resistance (Factor 5) pose significant obstacles to the implementation of reform. Additionally, the study emphasizes the need for continuous learning, leadership development, and adaptive governance strategies (Factor 6) to ensure the long-term sustainability of reforms. The variety of stakeholder perspectives indicates a complex interaction of ethical considerations, political dynamics, bureaucratic structures, and professional development needs. This research contributes to the discourse on public sector transformation by offering policy recommendations for ethical leadership, merit-based policies, and professional capacity building. Future studies should investigate these dynamics across different governance systems to reinforce institutional reforms worldwide.